2018
DOI: 10.1111/padm.12399
|View full text |Cite
|
Sign up to set email alerts
|

Structural reform histories and perceptions of organizational autonomy: Do senior managers perceive less strategic policy autonomy when faced with frequent and intense restructuring?

Abstract: Through recurrent structural reform programmes governments are on a quest to design public organizations that will stand the test of their environment. One of the approaches to uncertain or sensitive issues has been to create various forms of (semi‐)autonomous organizations with substantial strategic discretion. However, while governments repeatedly experiment with designs, one might simultaneously expect that such interference through repeated structural change may limit the degree of strategic policy autonom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…Severe disruption (e.g., in the form of repeated structural reform) within an agency may make both its senior management and subordinate civil servants increasingly risk averse (’t Hart and Wille 2006). While scholars interested in de facto autonomy have found that such disruption may thus reduce perceptions of autonomy (Kleizen et al ), we posit that it is also likely that they may increase the attention devoted to signals, as the organization's management attempts to safeguard the organization's stability.…”
Section: Theoretical Frameworkmentioning
confidence: 90%
See 3 more Smart Citations
“…Severe disruption (e.g., in the form of repeated structural reform) within an agency may make both its senior management and subordinate civil servants increasingly risk averse (’t Hart and Wille 2006). While scholars interested in de facto autonomy have found that such disruption may thus reduce perceptions of autonomy (Kleizen et al ), we posit that it is also likely that they may increase the attention devoted to signals, as the organization's management attempts to safeguard the organization's stability.…”
Section: Theoretical Frameworkmentioning
confidence: 90%
“…However, previous work already indicates that political actors have a strong urge to steer their implementing organizations, even when these organizations are placed at some distance from the government (’t Hart and Wille 2006; Kleizen et al ). As many formal control mechanisms that allow for ad hoc steering, such as the competence to provide direct and binding instructions, are not available towards formally autonomous agencies, political actors may resort to intervening through structural reforms altering the tasks, legal statute and organizational framework underpinning the agency (Carpenter ; Hood and Lodge , p. 184; Terman ; Zito ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One approach has been to test whether an organization can be designed or 'hardwired' to survive. Prominent design factors are legislative design and formal autonomy (Lewis 2003;Carpenter and Lewis 2004;Boin et al 2010;Park 2013;Greasley and Hanretty 2016;James et al 2016;Kleizen et al 2018). While these factors matter (Lewis 2003), they do not tell the whole story.…”
Section: Why Do Public Organizations Survive (Or Not)?mentioning
confidence: 99%